Senior nursing student’s confidence in learnt competencies and perceptions of patient safety competency: a multisite cross-sectional study - Mohammad Asghari Jafarabadi; Vahid Zamanzadeh; Leila Valizadeh; Akram Ghahramanian; Mostafa Ghasempour; Tonia C Onyeka (BMJ Open)
Objective Nursing students’ attainment of patient safety (PS) competency has always been a global concern among health and educational organisations. Therefore, this study was conducted to determine senior nursing students’ confidence of their PS competencies, and associated predictive factors.Design Cross-sectional study.Setting Four faculties from the nursing faculties of East Azerbaijan province.Participants 253 senior nursing students in Iran.Primary and secondary outcome measures Using the modified version of the Health Professional Education Patient Safety Survey, data related to the level of confidence of nursing students in acquired competencies in seven sociocultural dimensions of PS in classroom learning and clinical settings were collected. In addition, the predictors of the patient’s safety competencies were identified by linear regression statistics.Results Mean scores of all dimensions of PS competencies both in the classroom and in clinical settings were higher than 3.11 (out of 5). The nursing students were most confident in their learning of ‘understanding human and environmental factors’ in the classroom and the clinical setting. Nursing students displayed the least confidence in learning ‘work in teams with other health professionals’ in both the classroom and the clinical settings. Type of university, prior experience with PS competencies education, and coverage of PS competency issues in the curriculum predicted the students’ perceived competency scores in the classroom (R2=0.53, p<0.001). Also, perceived competence in the clinical settings was predicted by the variables of reporting errors to personnel and peers and the type of university (R2=0.65, p<0.001).Conclusion Study findings emphasise the role of learning environments and educational experiences of nursing students especially the clinical environment, clinical instructors and the hidden curriculum in improving safety competence. Nursing educators can use this information to revise and develop the undergraduate nursing curriculum, paying close attention to lesson plans and content in relation to teaching safety issues.